Selenium WebDriver with Java : novice to ninja plus interview (Packt Publishing, 2018)
"This course includes a wide range of basic and advanced topics from Selenium WebDriver; Java concepts TestNG framework; automation framework design (page objects, page factory, data-driven, reading Excel files); logging with Log4j, best reporting tool - Advanced Reporting; cross-browser testing with Selenium Grid 2.0; Maven build management; continuous integration with Jenkins; Git integration with Jenkins; database testing; performance testing; behavior- driven testing using Cucumber; Sauce labs integration and interview preparation. All materials are provided including code files. This is your one stop shop to become an expert in web automation framework related technologies from scratch. We start from beginners level and go through to advanced level. This is a single course for everything you need to know related to Web UI Automation. We assume that students have no experience in automation/coding and start every topic from scratch and basics. Examples are taken from testing real-time hosted web applications to understand how different components can be automated, and will give you an idea of the industry level framework confidence to use them. No prior coding or automation experience needed, this course covers all the necessary topics. We start with how to code in Java and then move towards learning Selenium, TestNG, Selenium grid, log4j, Maven, Jenkins, database testing, performance testing, and behavior-driven testing using Cucumber and Gherkin languages."--Resource description page